Care of the Patient With Acute Ischemic Stroke (Endovascular/Intensive Care Unit-Postinterventional Therapy): Update to 2009 Comprehensive Nursing Care Scientific Statement. Issue 5 (May 2021) - Rodgers, Mary L.; Fox, Elizabeth; Abdelhak, Tamer; Franker, Lauren M.; Johnson, Brenda Joyce; Kirchner-Sullivan, Christina; Livesay, Sarah L.; Marden, Franklin A.
Abstract : Ischemic stroke remains the fifth leading cause of death in the United States. Nurses play a pivotal role in the care of patients throughout the continuum. With the advances in stroke care, including mechanical thrombectomy, the American Heart Association/American Stroke Association charged the writing panel to complement the 2009 clinical practice guideline, "Comprehensive Overview of Nursing and Interdisciplinary Care of the Acute Ischemic Stroke Patient, " with current evidence-based nursing care. This update is 1 of a 3-part series focusing on emergency medical services/emergency care, endovascular/intensive care unit care, and postacute care. The aim of this scientific statement is to review and present current evidence, complications, best practices, and clinical practice strategies to provide current comprehensive scientific information for nursing care in the neuroendovascular area and intensive care unit in conjunction with medical treatments, including intravenous thrombolysis and mechanical thrombectomy.